PLACE AND ROLE OF WOMEN IN THE MEDIA IN IVORY COAST : AN EGALITARIAN PRINCIPLE STILL PROBLEMATIC - Ibitowa, Philippe (International Journal of Multidisciplinary Research and Studies, 2022)
If there are major issues that concern our contemporary society, one cannot help citing, among the priorities, the question of the advancement of women and of parity. Indeed, for decades, following the first world conference on the status of women in Mexico City in 1975, it is recognized that a society cannot experience integral, sustainable, and harmonious development without the consideration and participation of women. From the rural world to the city, the role and place of women in all sectors of activity are regularly analyzed with a view to learning about their evolution over time. Similarly, the Fourth World Conference on Women held in Beijing in 1995, under the theme “Equality, Development and Peace”, developed an action plan defining twelve (12) Priority areas including the media where measures were deemed necessary to achieve gender equality. Through this article, we try to assess the impact of such initiatives in favor of the emancipation of women in Ivorian society, especially in the media sector. Our study covered 22 news organizations from all sectors (television, press, radio, press agency, and online media). With the theory of naturalistic thought or the sexual division of labor, and based on interviews with 56 media women and/or their editors, we try to understand the place, the role, and the activities of women in the Ivorian media, as well as the representations made of them. The results of our research show that, despite some progress, the media world in Ivory Coast still remains unequal in terms of parity, in the image of the entire Ivorian society.